SISTEM INFORMASI PENJUALAN PEMBELIAN DAN STOK BARANG BERBASIS WEBSITE PADA TOKO BUKU ANGGIE CIBUBUR - Anisah Fitri Nurkhasanah, (2022)
There are still many information systems on bookstore sales that are done manually and not computerized, namely by using sales made manually by recording items that are sold, stock of goods, and calculating prices manually by employees. Anggie Bookstore is a bookstore that sells all kinds of school, office, uniforms, children's toys, cloth dolls at wholesale and retail prices. The system used at Anggie's bookstore still uses a manual system using paper notes for each transaction and stock of goods. In this study, the authors use the waterfall system design method and PIECES analysis using the Data Flow Diagram (DFD) concept to make it easier for programmers to create systems to make the system run and propose. This system is designed using the PHP programming language and MySQL database. The result of this research is that the existence of an information system at the Anggie Bookstore can make it easier for admins to save files and can view sales and purchase reports at any time. Keywords: Anggie Bookstore, Information Systems, Sales and Stocks, Website.